TINJAUAN AKAD IJARAH TERHADAP JASA PACAK KUCING DI PONDOK KUCING EDELWEIS PONTIANAK - Irda Andini; Dahlia Haliah Ma'u; Nur Hakimah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
The purpose of this research is to find out the practice of cat pacak services at Pondok Kucing Edelweis Pontianak and study it based on the ijarah contract. This research uses a qualitative method with the type of empirical or field legal research. The main data sources include interviews with the owner and consumers of Pondok Kucing Edelweis Pontianak shop. Meanwhile, secondary data used are books, journals, theses, and websites that discuss cat pacak. Data collection techniques used were interviews, observation and documentation. Data validity was checked through source triangulation. The results showed that the practice of cat trapping services at Pondok Kucing Edelweis Pontianak uses a rental contract (ijarah). The cat trapping process involves the owner of the male cat as the provider of cat trapping services and the owner of the female cat as the consumer. The review of the ijarah contract on the practice of cat tracking services seen from the pillars and conditions of the ijarah contract is invalid because in the practice of cat tracking services, one of the conditions of ijarah is not fulfilled, namely the benefits in the form of sperm where the males hired to marry females are unclear about the amount of sperm and whether marriage can occur or not, thus causing a violation of gharar because it is unclear about the substance, nature and size of the sperm, so it cannot be handed over. According to the majority of scholars, it is forbidden to hire cat breeding services for a fee.